A Historiography of Babur to Aurangzeb in the Mughal Empire: Exploring the Social, Cultural, and Artistic Aspects of Mughal India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the present theory an endeavor has been made to consider the social set up and culture in Mughal India. The accentuation of the proposal is on strict patterns and thought, Sufi and Bhakti, social condition, language and writing, engineering and painting, and expressive arts and so forth. I needed to cover an immense research through observational, philosophical and national request. It has been seen troublesome as both extensive and escalated. Some work has been done on the social history of Mughal India, yet no orderly investigation has been made. This postulation is an unassuming endeavor to fill this hole is our investigations. The source material for the examination is fluctuated and dissipated. What we have is a progression of impressions outfitted by Persian narratives, voyagers accounts and indigenous authors, who noted what appeared to them of intrigue. The assistance structure the auxiliary sources is additionally taken.